The A to Z of the Philippines - Guillermo, Artemio R.; May Kyi Win.; Guillermo, Artemio R. (Lanham, Maryland Scarecrow Press, 2010)
"The A to Z of the Philippines provides more than 400 hundred entries on important persons, places, events, and institutions, as well as salient economic, social and cultural aspects."--Publisher's description.
Originally published as: Historical dictionary of the Philippines. 2005.
Keywords: Philippines -- History -- Dictionaries